Proteinuria-Lowering Effects of Proprotein Convertase Subtilisin/Kexin Type 9 Inhibitors in Chronic Kidney Disease Patients: A Real-World Multicentric Study - Patricia Muñoz Ramos; Yohana Gil Giraldo; Vicente Álvarez-Chiva; David Arroyo; Cristina Sango Merino; Francesc Moncho Francés; Javier Ocaña; Javier Reque; Emilio Sánchez-Álvarez; José Luis Górriz; Borja Quiroga (Metabolites, 2021)
Control of dyslipidemia in chronic kidney disease (CKD) is not always guaranteed with statins and/or ezetimibe. Proprotein convertase subtilisin/kexin type 9 inhibitors (PCSK9i) have opened up a new era in lipid control, but their effect on renal function and proteinuria in real life have not yet been evaluated. The aim of the present study was to analyze the evolution of renal function and proteinuria in a cohort of CKD patients treated with PCSK9i. This retrospective multicentric cohort study included CKD patients treated with PCSK9i. Baseline epidemiological data, comorbidities and laboratory findings (including estimated glomerular filtration rate [eGFR], proteinuria and lipid profile) were collected. The evolution of renal function, proteinuria and lipid profile was analyzed during the 1-year follow-up. The cohort included 76 patients (68% male, mean age 66 ± 10 years). The mean baseline creatinine was 1.55 ± 0.77 mg/dL, and the mean eGFR was 52 ± 22 mL/min/1.73 m2. Reductions in LDL-cholesterol, total cholesterol and triglycerides during the first month were 51 ± 25%, 32 ± 25% and 11 ± 40%, respectively, levels that remained stable throughout the first year (p < 0.001 for LDL-cholesterol and total cholesterol trends and p = 0.002 for triglyceride trend). During follow-up, proteinuria improved from 57 (9–481) to 30 (7–520) mg/g (p = 0.021). In addition, eGFR remained stable, and no adverse events were reported. In our cohort, dyslipidemia treatment with PCSK9i was associated with decreased proteinuria in CKD patients, an effect that might be due to reduced lipid nephrotoxicity. Clinical trials are needed to further investigate whether this impact on proteinuria can significantly slow CKD progression in the long term.